Analisis Pemanfaatan Media Sosial TikTok Dalam Membangun Brand Awareness PT. Citra Sukses Entertainment - Kresna, Donny; Abidin, Sholihul (SCIENTIA JOURNAL, 2024)
In the current digital era, of course we can never be separated from life related to the digital world where this has become part of our social life. Social media of course plays a big role in providing benefits, because the function of social media is not only limited to making friends or meeting other people, but can also be used for many things, one of which is trading or selling. Marketing strategy is the marketing stage of a product or service where a member or organization carries out the planning stage regarding exchanges so that they can find out the right target population and can achieve their own goals, one of which is profit. Brand Awereness is a marketing technique used by business people to win market competition and make their company known to the public. In this descriptive analysis, the data that has been collected will be described and depicted descriptively. In creating product promotion methods, we have unconsciously produced 4 types of methods, namely Advertising, Events & Experience, Direct Marketing and Interactive Marketing.